2015
DOI: 10.2135/cropsci2014.05.0403
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic Impact of a Stem Solidness Gene in Near‐Isogenic Lines of Wheat

Abstract: The primary trait in wheat (Triticum aestivum L.) to prevent damage caused by the wheat stem sawfly (WSS) (Cephus cinctus) is antibiosis facilitated by solid stems. The pith of solid stems impedes development of larvae, often resulting in their death inside the stem. A key question regarding solid stems is the possible impact on grain yield potential due to photosynthate partitioning to stem pith instead of to grain. Molecular markers for the major gene controlling stem solidness, Qss.msub‐3BL, were used to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 29 publications
1
14
1
Order By: Relevance
“…Sequence information for the sequence‐based SNPs that were found to be associated with solid stems in this study can be found in Supplemental Table S1. Lastly, previous studies found no significant correlation between yield and the solid‐stem trait (Cook et al, 2004; Sherman et al, 2015), but in this study, a significant negative correlation of −0.25 ( P < 0.05) was identified between the solid‐stem trait and yield in rainfed environments (Table 2). The significant negative correlation found in this study between the solid‐stem trait and yield demonstrates that solid‐stem varieties may suffer a yield penalty in some genetic backgrounds and environments.…”
Section: Discussioncontrasting
confidence: 54%
“…Sequence information for the sequence‐based SNPs that were found to be associated with solid stems in this study can be found in Supplemental Table S1. Lastly, previous studies found no significant correlation between yield and the solid‐stem trait (Cook et al, 2004; Sherman et al, 2015), but in this study, a significant negative correlation of −0.25 ( P < 0.05) was identified between the solid‐stem trait and yield in rainfed environments (Table 2). The significant negative correlation found in this study between the solid‐stem trait and yield demonstrates that solid‐stem varieties may suffer a yield penalty in some genetic backgrounds and environments.…”
Section: Discussioncontrasting
confidence: 54%
“…A recent genetic study using near-isogenic lines for the Qss.msub-3BL showed that the allele for solid stems did not have a negative effect on grain yield (Sherman et al, 2015) based on yield trials conducted over nine environments. Limitations constraining other potential control measures have driven pest management efforts toward resistance breeding.…”
Section: Discussionmentioning
confidence: 99%
“…This is likely due to the introduction of stem solidness into germplasm of the Northern Great Plains in the middle of the 20th century and subsequent introgression of the genes for stem solidness into lines targeted specifically for WSS-impacted areas. A recent genetic study using near-isogenic lines for the Qss.msub-3BL showed that the allele for solid stems did not have a negative effect on grain yield (Sherman et al, 2015) based on yield trials conducted over nine environments. However, there was also no advantage to the allele for solid stems in the absence of WSS, thus, the solid stem allele is absent or present at low frequencies in most germplasm.…”
Section: Discussionmentioning
confidence: 99%
“…28 Increased resistance of wheat to C. cinctus has been accomplished by developing solid-stemmed cultivars that reduce egg deposition and decrease survival of eggs and larvae. 5,[29][30][31] However, solid-stem wheat cultivars often yield less than the traditional hollow-stemmed cultivars 5,32,33 (but see Sherman et al 34 ) and limit parasitism of C. cinctus 35 (but see Weaver et al 18 and Wu et al 36 ). Because penetration of the stem and host location are more difficult for parasitoids; 37 the efficacy of hollow-stemmed wheat is also dependent on the availability of preferred alternative hosts.…”
Section: Introductionmentioning
confidence: 99%